Hubungan Filsafat Agama Dan Moderasi: Filsafat Agama, Moderasi, Beragama, Toleransi - Nila Fadilah Nasution (Jurnal Penelitian Multidisiplin, 2022)
Indonesia as a multicultural country that has various tribes, cultures, and religions is a wealth to be proud of and grateful for. However, this plurality sometimes gives rise to various understandings, especially in religious understanding. So that this can lead to intolerant conflicts in the midst of this plural society situation. Therefore, this research encourages to describe the idea of ​​philosophy of religion as the basis for logical thinking and understanding religion universally, deeply, and systematically. The method used in this research is library research, namely tracing and examining data or information related to the research discussion. This study aims to provide an understanding that religion needs to be based on moderate values ​​in this case as an effort to create harmony between religious communities. Thus, the study concludes that the construction of religious moderation values ​​aims as an effort to moderate religious attitudes by choosing the middle way to realize social harmony and balance of life.